Market Penetration and Branding Strategy as a Basis for Managerial Decision Making to Increase Sales of Prim-A Mineral Water - Muhammad Ammar Faras; Utomo Sarjono Putro (Al-Makki Publisher, 2026)
The bottled drinking water market in Indonesia is highly competitive, prompting PT Sinar Sosro Gunung Slamat to strengthen Prim-A mineral water as a strategic diversification product amid declining ready-to-drink tea sales. Despite contributing Rp42.7 billion in Bandung in 2025, Prim-A ranked only 30th nationally in bottled water distribution, leading management to target a doubling of sales by 2026. This study aims to formulate an integrated distribution and branding strategy to increase Prim-A sales in Bandung. A qualitative approach was employed using data triangulation through semi-structured interviews with six key informants, observations at 15 retail outlets, and internal distribution data from 1,013 active outlets during January–December 2025. Data were analyzed using Numeric Distribution, All Commodity Value, Keller’s Customer-Based Brand Equity (CBBE) framework, Pareto analysis, and SWOT analysis. The findings reveal two major challenges. First, Prim-A’s Numeric Distribution reached only 3.91%, indicating substantial untapped market potential, while Pareto analysis showed revenue concentration in a limited number of outlets and significant contributions from wholesale channels. Second, the CBBE analysis identified weaknesses across all brand equity dimensions, particularly in the trial stage, as consumers who had never tried Prim-A tended to prefer more established competitors. The association between Prim-A and Sosro was also insufficiently communicated. Based on these findings, an integrated 12-month strategy was developed, focusing on selective retail expansion, food service development, wholesale channel optimization, targeted product sampling, stronger in-store branding, and consistent communication of the Prim-A–Sosro relationship. The projected implementation is expected to achieve 189.2% of the 2025 revenue, exceeding the company’s double-sales target.